Is there a difference in the positioning of sliding screws between stable and unstable extracapsular fractures? - Pedro José Labronici; Rodrigo Freitas da Silva; Ana Maria Santos Viana; Saulo Santos Blunck; José Sergio Franco; Sergio Ricardo Neto; Robinson Esteves Santos Pires; Roberto Canto (Revista Brasileira de Ortopedia, 2015)
OBJECTIVE: To analyze the tip-apex distance (TAD), cervicodiaphyseal angle and Garden angle in stable and unstable extracapsular fractures of the femur treated with a plate and sliding screw.METHOD: Hip radiographs in anteroposterior (AP) and lateral view on 117 patients were evaluated. The fractures were classified as stable or unstable, using the AO classification, and the reduction achieved was assessed in accordance with the following criteria: TAD > 3 cm; Garden alignment index (AP) < 160°; and AP cervicodiaphyseal varus angle < 125°. When two or more criteria were present, the quality of the osteosynthesis was classified as "not ideal".RESULTS: The patients with unstable fractures presented AP cervicodiaphyseal angles that were significantly greater (p = 0.05) than in those with stable fractures. The patients with unstable fractures presented lateral cervicodiaphyseal angles that were significantly smaller (p = 0.05) than in those with stable fractures. There were no significant differences in the remainder of the criteria evaluated.CONCLUSION: This study did not find any significant differences in the measurements evaluated, except in relation to the cervicodiaphyseal angle. Satisfactory reduction was achieved both for the stable and for the unstable fractures, when we used a plate and sliding screw to treat proximal extracapsular fractures of the femur.